Impact of GA3 on corm nutrient and yield of gladiolus (Gladiolus hortensis) (cv. Punjab Dawn) - MAURYA, RAGINI; K SINGH, ANIL (The Indian Journal of Agricultural Sciences, 2022)
Nutrient status in gladiolus corms were assessed following GA3 treatment and number of bud of corm (cut as well as whole corm). The experiment was laid out in randomized block design involve factorial combination with three replications. Result revealed that 5 bud and GA3 200 ppm showed maximum (10.99% and 9.24%) nitrogen uptake whereas phosphorus accumulation (17.26% and 21.88%) was recorded maximum in 200 ppm GA3 and 6 bud corm and 5 bud with 200 ppm GA3 gave maximum (11.93% and 15.87%) potassium content. Minimum (3.36% and 5.37%) nitrogen accumulation was exhibited with 1 bud and control and 2 bud and 100 ppm GA3 application, in context of phosphorus, minimum (4.25%) and (7.11%) was observed with 1 bud and control (distilled water) corms and also potassium uptake was least (2.75%) and (3.90%) in 1 bud and 200 ppm GA3. Similarly corm and cormel parameters were influenced by whole corms which were treated with 200 ppm GA3 in the both year of experiment. Hence, whole corm as well as higher concentrations of GA3 (200 ppm) enhanced uptake of N, P, K in harvested gladiolus corm as well as corm yield due to potential of enhancing the source-sink relationship.